Transformasi Model Bisnis Museum Ke Pariwisata Digital Di Indonesia - Devinta Nur Arumsari; Muhadjir Anwar; Dominikus Aditya Fitriyanto (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
Background – Because of the Covid-19 pandemic, human travel was severely restricted and reliant on digital technology. Tourism is one of the businesses that has been obliged to adapt to digitalization in order to keep its primary source of income from travelers. The present transition to digital tourism is taking the shape of virtual tours or long-distance interactive tours, such as those seen in museums. To reach more tourists, some museums in Indonesia already entered the digitization stage by offering virtual tours and edutainment. Aim – This study intends to provide emphasis on the advantages and disadvantages of disruptive innovation in the sense of digitization in the tourism industry, particularly museums. Design / Methodology / Approach – An detailed review of existing literature regarding digital technology, disruptive digital innovation, smartphone technology, social media, internet, and mobile applications from the perspective of museum tourism was used. Findings – Digital museums provide a new perspective to enjoy their collections and as a diversification strategy that has the potential to bring in tourists virtually. Curators should develop websites using communication strategies that relate to their collection and focus on their visitor profile. On the other hand, there is a risk that there is a conservative opinion that digitization will reduce the integrity of physical artwork and an unstable digital ecosystem. Conclusion - The digitization and publication of collections online has the potential to enable access to content. It is projected that disruptive innovation in the form of changing the museum's business model will provide financial benefits and become a business diversification that can support the sustainability of the museum itself in the future. Research implication – In the field of management, disruptive innovation in the form of changing the museum's business model will provide financial benefits and become a business diversification that can support the sustainability of the museum itself in the future. In the field of architecture, the preservation of cultural heritage objects through digitization guarantees digital archives and provides wider educational opportunities virtually. Research Limitations – The breadth of coverage regarding the digitization of museums and also the many things that still need to be done in order to implement it perfectly, makes research on digitization will continue to be needed. Future studies can complement and continue to update research results so that museums can also continue to evolve.